Exploring safety culture and speeding among truck drivers: A study in Johor / Zamri Miskam …[et al.] - Miskam, Zamri; Abdul, Saiful Azlan; Mahmud, Nurazree; Wahab, Samsudin (Universiti Teknologi MARA Cawangan Pahang, 2020)
The phenomenon of speeding among truck drivers are prevalent in most places and contributed to high number of road accidents. Most of heavy vehicle drivers are subjected to multiples traffic laws including their employers for monitoring safety performance while discharging duties. However, heavy vehicle drivers or truck drivers are in full control of their behaviour and as such reckless driving or speeding are all due to their attitudes, which resulted to such behavioural actions. The current study is looking at redefining safety culture in exploring the behaviours of speeding among heavy vehicle drivers. Multiple series of case studies, comprising interviews as well as observations were conducted at three road transport operators to explore the effect of safety culture in these organisations. The findings for the inappropriate speed are documented and discussed. It was discovered that transport organisations which implemented the driver’ performance monitoring on over speeding either through internal initiative or authorities enforcement could all reduce the likelihood of over speeding among truck drivers. Nonetheless, due to flaws in the ability to monitor appropriate speed, this conduct was primarily influenced by attitudes, values and cultural beliefs. Truck drivers are generally have the tendency to regard speed as relatively safe and as such , had the determination to speed to cut down time and increase delivey trips, and therefore often attempted to speed without detection.Generally drivers perceived speeding as risk, however they were prefer to drive safely. Consequences for intervention are discussed.